Estratificação do risco cardiovascular em obesos e sua relação com modulação autonômica cardíaca, risco para apneia obstrutiva do sono e funcionalidade - Brandão, Marconi Pereira (2024)
Obesity and obstructive sleep apnea (OSA) have a bidirectional relationship and common risk factors associated with adverse cardiovascular events. This close relationship is linked to impaired functioning, autonomic cardiac dysfunction, and the onset of cardiovascular diseases. Given the potential health impact of these conditions, the first study aimed to identify the risk of cardiovascular events through the stratification of the Framingham score and to relate it to autonomic cardiac modulation, OSA risk, and functioning in individuals with obesity. The results showed that in the FRAMINGHAM outcome, obese individuals have greater mobility impairment and a high risk of OSA, which is directly related to a moderate to high risk of experiencing a cardiovascular event within 10 years. The second study aimed to investigate the interaction between the risk of OSA and obesity and how this relationship influences autonomic cardiac modulation and functioning. The data indicated that in the STOP-Bang outcome, individuals with obesity have a high risk of OSA and poor sleep quality. Furthermore, these patients have greater restrictions on self-care due to the risk of OSA. These findings suggest that an increased risk of OSA may promote a decrease in HRV and greater sympathetic activity. Both cross-sectional studies offer perspectives on cardiovascular risk and OSA, providing relevant insights for healthcare professionals to use in the evaluation and monitoring of the clinical status of the studied population.